The Significance of Secreted Phosphoprotein 1 in Multiple Human Cancers - Wei, Tengteng; Bi, Guoshu; Bian, Yunyi; Ruan, Suhong; Yuan, Guangda; Xie, Hongya; Zhao, Mengnan; Shen, Rongming; Zhu, Yimeng; Wang, Qun; Yang, Yong; Zhu, Donglin (Frontiers in Molecular Biosciences, 2020)
Cancer is one of the leading causes of mortality worldwide and its incidence is growing rapidly. Developing early diagnostic tools may be an effective way to increase the chances of survival and provide more treatment opportunities. Secreted phosphoprotein 1 (SPP1), also called Osteopontin (OPN), has been demonstrated overexpressed in many cancers. However, the specific role of SPP1 in prognosis, gene mutations, and changes in gene and miRNA expression in human cancers is unclear. In this report, we found SPP1 expression was higher in most of the human cancers. Based on Kaplan-Meier plotter and the PrognoScan database, we found high SPP1 expression was significantly correlated with poor survival in virous cancers. Using a large dataset of colon adenocarcinoma (COAD), head and neck cancer (HNSC), lung adenocarcinoma (LUAD), and lung squamous cell carcinoma (LUSC) patients from The Cancer Genome Atlas (TGCA), and Gene Expression Omnibus database (GEO), we identified 22 common genes and 2 common miRNAs. GO, and KEGG paths analyses suggested that SPP1 correlated genes were mainly involved in positive regulation of immune cell activation and infiltration. SPP1-associated genes and miRNAs regulatory networks suggested that their interactions may play a role in the progression of four selected cancers. SPP1 was significantly positively correlated with infiltrating levels of immune cells, and immune marker sets. All of these data provide strong evidence that SPP1 may promote tumor progress through interacting with carcinogenic genes and facilitating immune cells’ infiltration in COAD, HNSC, LUAD, and LUSC.